Estado actual y proyección de la investigación relacionada con mancha angular del frijol (Phaeoisariopsis griseola) - Jara, Carlos E.; Castellanos, G.; Mahuku, George S. (2001)
Angular leaf spot of common bean, Phaseolus vulgaris L., is caused by the fungus Phaeoisariopsis griseola (Sacc.) Ferraris. This disease is widely distributed in tropical and subtropical countries where it affects pod quality and cause high yield losses. Because knowledge of the genetic diversity and pathogenic variation of the pathogen is nec essary for the identification of durable sources of resistances for a breeding program, we used a set of 12 common bean differential varieties to characterize 419 P. griseola isolates collected from differ ent zones and countries of the world were beans are grown. All iso lates from Africa and Latin America were distributed into two large groups, Andean and Mesoamerican that were highly correlated to common bean gene pools. Only 21 of the 120 races identified were found in more than one country, where as 71 were only found in one country. Some races (68) were present only in Latin America while 31 races were found only in Africa, showing that use of resistant varieties to manage angular leaf spot can be specific for different regions. Evaluations of germplasm accessions and advanced lines resulted in 11 genotypes that were resistant to the most virulent race (63-63) under greenhouse conditions. These genotypes constitute potential sources of resistance genes for a breeding program and should be evaluated under field conditions in different regions where ALS is an important production constraint.